1991
DOI: 10.1063/1.348765
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of surface acoustic wave propagation on {100}-cut 〈110〉-propagating gallium arsenide

Abstract: Articles you may be interested inReflection characteristics of obliquely incident surface acoustic waves from groove and aluminum gratings on {100}-cut gallium arsenide Surface acoustic waves on the (11n) cuts of gallium arsenide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…δ is the thermal expansion coefficient. *There seems to be some disagreement between different articles 24,31,32 .…”
Section: A Materials For Quantum Saw Devicesmentioning
confidence: 99%
“…δ is the thermal expansion coefficient. *There seems to be some disagreement between different articles 24,31,32 .…”
Section: A Materials For Quantum Saw Devicesmentioning
confidence: 99%
“…The research claimed that during the application of light pulses, electrons were separated from holes, picked up by SAW, and collected at the output, yielding an efficiency of 0.09 for the acoustic-opto device [130]. The SAW propagation in the <110> direction on GaAs with a l00-cut was used in the non-destructive sensing (NDS) array setup by Hunt et al [125] in 1990 to transmit charge in discrete packets, as shown in figure 21(b). These non-destructive arrays are capacitively connected to the charge packets.…”
Section: Within Inorganic Semiconductorsmentioning
confidence: 99%